Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1967
DOI: 10.1149/1.2426732
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Propane Adsorption on Platinum in Hydrofluoric Acid

Abstract: As a first stage in the investigation of the electrochemical oxidation of saturated hydrocarbons on platinum in acid electrolytes, the rate of adsorption of propane on a smooth platinum electrode was studied at 90~ in 37 mole % HF. Using an all-PTFE apparatus and single linear voltage sweep techniques, the surface coverage by hydrocarbon species was measured as a function of adsorption time and potential. The steady-state coverage resulting from propane adsorption shows a sharp maximum at 0.2v (vs. rhe). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
0

Year Published

1968
1968
1972
1972

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 16 publications
7
40
0
Order By: Relevance
“…The first portion of this study showed that the rate of propane adsorption on platinum in hydrofluoric acid at 90~ is consistent with Langmuir kinetics, third order in free surface at both 0.2 and 0.3v vs. a reversible hydrogen electrode in the same electrolyte (rhe) (22). The formation of a highly electroactive species from the initially adsorbed "propane" was also reported (22).…”
supporting
confidence: 70%
See 4 more Smart Citations
“…The first portion of this study showed that the rate of propane adsorption on platinum in hydrofluoric acid at 90~ is consistent with Langmuir kinetics, third order in free surface at both 0.2 and 0.3v vs. a reversible hydrogen electrode in the same electrolyte (rhe) (22). The formation of a highly electroactive species from the initially adsorbed "propane" was also reported (22).…”
supporting
confidence: 70%
“…1) in order to bring the electrode to a reproducible condition and prevent the accumulation of hydrogen or oxygen in the vicinity of the electrode. (22) and is similar to that used by Gilman (13) in related investigations. The potential was then stepped to 1.2v in order to maintain the oxide layer while the appropriate mass transport conditions were established (portion C of voltage sequence).…”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations